Seafloor geomorphology as benthic habitat : GeoHAB atlas of seafloor geomorphic features and benthic habitats - Harris, Peter T. (Peter Townsend), 1958-; Baker, Elaine K., 1957- (Elsevier, 2020)
Seafloor Geomorphology as Benthic Habitat: GeoHab Atlas of Seafloor Geomorphic Features and Benthic Habitats, Second Edition, provides an updated synthesis of seabed geomorphology and benthic habitats. This new edition includes new case studies from all geographic areas and habitats that were not included in the previous edition, including the Arctic, Asia, Africa and South America. Using multibeam sonar, the benthic ecology of submarine features, such as fjords, sand banks, coral reefs, seamounts, canyons, mud volcanoes and spreading ridges is revealed in unprecedented detail. This timely release offers new understanding for researchers in Marine Biodiversity, environmental managers, ecologists, and more.